The Essence of the Concepts of Local Budget and Deputy Control (Zien Journal of Social Sciences and Humanities, 2023)
This article focuses on the concept of the local budget and the essence of the content. At the same time, an attempt was made to cover the issues of income and expenses of local budgets in our country. The history and chronology of the formation of local budgets is presented. The article reveals the importance of the establishment of parliamentary control over local budgets today in the well-being of the country and the population. It is based precisely on ensuring the stability of society, serve to strengthen the trust of individuals in public administration.